The Effectiveness of Fiqh Learning on Students' Worship Practices at Madrasah Tsanawiyah - Khairun Nisa, Akma; Munira RKT, Siska Lailan; Sabri, Ahmad; Hidayatullah, Rully (IDRIS Darulfunun Institute, 2024)
This study aims to thoroughly investigate the effectiveness of fiqh learning on students' worship practices at MTsN 2 Agam. With the continuous growth in religious education, a strong understanding of Islamic teachings becomes increasingly important for students in educational institutions like MTsN 2 Agam. Fiqh, as a branchq of Islamic knowledge that studies practical laws and rules of worship, forms the core of the religious curriculum in this school. This study will explore the extent to which fiqh learning in fiqh classes at MTsN 2 Agam influences students' understanding of worship practices such as prayer, fasting, and almsgiving. Emphasis will be placed on the practical guidance imparted in fiqh learning, which includes correct techniques and procedures in performing these rituals. Additionally, the study will observe how a strong understanding of religious principles, taught through fiqh learning, impacts students' daily lives outside the school environment. Through careful data collection and analysis, this research aims to provide a better understanding of how fiqh learning at MTsN 2 Agam influences students' worship practices. The findings of this research are expected to provide valuable insights for the development of religious curricula in similar educational institutions and also shed light on the importance of fiqh education in shaping individuals who are obedient to religious teachings and reflect high moral values and ethics in their interactions with others.